Chlorophyll meter- and leaf color chart-based nitrogen management for rice and wheat in northwestern India - Singh, Bijay; Singh, Yadvinder; Ladha, Jagdish K.; Bronson, Kevin F.; Balasubramanian, Vethaiya; Singh, Jagdeep; Khind, Charan S. (Wiley, 2002)
Overapplication of N in cereal crops leads to low N recovery efficiency and risk of NO3 pollution of ground water. The chlorophyll meter, also known as SPAD meter, is a simple, portable diagnostic tool for identifying crop N status. We used it to test need‐based N management approaches for rice (Oryza sativa L.) and wheat (Triticum aestivum L.) on a loamy sand in northwestern India. Applying 30 kg N ha−1 each time the SPAD value fell below the critical value of 37.5 resulted in application of 90 kg N ha−1, which produced rice yields equivalent to those with 120 kg N ha−1 applied in three splits. Using a SPAD value of 35 was inadequate for the two rice cultivars because it resulted in application of only 60 kg N ha−1 and, thus, low yields. With high inherent soil fertility resulting in rice yield of >3 Mg ha−1 in zero‐N plots, applying N basally or a week after rice transplanting did not further increase yield. Limited experimentation with leaf color chart (LCC) indicated that N management based on LCC shade 4 helped avoid overapplication of N to rice. Wheat responded to N application at maximum tillering (MT) when SPAD value fell below 44. Wheat yield increased by 20% when 30 kg N ha−1 was applied at SPAD value of 42 at MT. Results show that plant need–based N management through chlorophyll meter reduces N requirement of rice from 12.5 to 25%, with no loss in yield.